New Calisto species from Cuba, with insights on the relationships of Cuban and Bahamian taxa (Lepidoptera, Nymphalidae, Satyrinae) - Aguila, Rayner Núñez; Matos-Maraví, Pável F.; Wahlberg, Niklas (Zootaxa, 2013)
Three new species and a new subspecies of Calisto Hübner are described from Cuba, Calisto torrei sp. n. Núñez, Calisto dissimulatum sp. n. Núñez, Calisto aquilum sp. n. Núñez, and Calisto aquilum occidentalis ssp. n. Núñez. The immature stages of C. torrei and C. dissimulatum are also described. Notes on the distribution and biology of the species are given. All Cuban and Bahamian taxa form a monophyletic group which seems to have originated in northeastern Cuba spreading later to the west. DNA sequence data also allowed to recognize both Bahamian taxa, Calisto sibylla and Calisto apollinis stat. n., as distinct species, and to synonymize Calisto herophile parsonsi syn. n. under Calisto herophile.